2008
DOI: 10.1103/physreva.77.043408
|View full text |Cite
|
Sign up to set email alerts
|

ac electric trapping of neutral atoms

Abstract: We study the dynamic behavior of ultracold neutral atoms in a macroscopic ac electric trap. Confinement in such a trap is achieved by switching between two saddle-point configurations of the electric field. The gradual formation of a stably trapped cloud is observed and the trap performance is studied versus the switching frequency and the symmetry of the switching cycle. Additionally, the electric field in the trap is mapped out by imaging the atom cloud while the fields are still on. Finally, the phase-space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Schlunk et al demonstrated the trapping of 87 Rb atoms transferred from an MOT in a cylindrically symmetric AC trap with two ring-electrodes and two hemispherical electrodes [182,183]. Around 10 5 atoms were trapped at 100 µK.…”
Section: Ac Electric Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schlunk et al demonstrated the trapping of 87 Rb atoms transferred from an MOT in a cylindrically symmetric AC trap with two ring-electrodes and two hemispherical electrodes [182,183]. Around 10 5 atoms were trapped at 100 µK.…”
Section: Ac Electric Trapsmentioning
confidence: 99%
“…In the first step towards this goal, Schlunk and co-workers have demonstrated the successful transfer of magnetically trapped Rb atoms into an AC electric trap which could be used to confine Stark decelerated ammonia molecules [182,183]. As the magnetically trapped Rb atoms remain unaffected by the highfrequency electric fields suitable for confining ground state polar molecules, this type of experimental setup should be able to simultaneously trap both species and attempt sympathetic cooling.…”
Section: Sympathetic Coolingmentioning
confidence: 99%
“…There-Typeset by REVT E X arXiv:1109.6203v1 [physics.atom-ph] 28 Sep 2011 fore, the performance of an ac electric trap for groundstate CO molecules will be very similar to that of an ac electric trap for ground-state 87 Rb atoms. The latter trap has been demonstrated [12,13] and carefully characterized [14] before, from which it is concluded that ac electric traps with a depth of tens of micro-Kelvin can be made for ground-state CO molecules.…”
Section: Introductionmentioning
confidence: 95%